Dynamic patterns of histone lysine methylation in the developing retina - Rao, Rajesh C; Tchedre, Kissaou T; Malik, Muhammad Taimur A; Coleman, Natasha; Fang, Yuan; Marquez, Victor E; Chen, Dong Feng (Investigative ophthalmology & visual science, 2010)
Histone lysine methylation (HKM) is an important epigenetic mechanism that establishes cell-specific gene expression and functions in development. However, epigenetic control of retinal development is poorly understood. To study the roles of HKM in retinogenesis, the authors examined the dynamic changes of three HKM modifications and of two of their regulators, the histone methyltransferases (HMTases) Ezh2 and G9a, in the mouse retina. Retinal sections and lysates from embryonic day 16 through adult were processed for immunohistochemistry and immunoblotting using antibodies against various marks and HMTases. To further analyze the biological functions of HKM, the effects of small molecule inhibitors of HMTases were examined in vitro. Methylation marks of trimethyl lysine 4 and 27 on histone H3 (H3K4me3 and H3K27me3) were detected primarily in differentiated retinal neurons in the embryonic and adult retina. In contrast, dimethyl lysine 9 on histone H3 (H3K9me2) was noted in early differentiating retinal ganglion cells but was lost after birth. The HMTases controlling H3K27me3, H3K9me2, Ezh2, and G9a were enriched in the inner embryonic retina during the period of active retinogenesis. Using the chemical inhibitors of Ezh2 and G9a, the authors reveal a role for HKM in regulating retinal neuron survival. HKM is a dynamic and spatiotemporally regulated process in the developing retina. Epigenetic regulation of gene transcription by Ezh2- and G9a-mediated HKM plays crucial roles in retinal neuron survival and may represent novel epigenetic targets to enhance viability in retinal neurodegenerative diseases such as glaucoma.